Reevaluating Leadership Criteria in Village Governance: A Comparative Analysis of Law No. 3 of 2024 and Imam al-Mawardi’s Political Thought - Saputra, Dion; Maimun; Susilo, Edi (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
This study examines the implementation of Article 33 of Law No. 3 of 2024 concerning village governance, analyzing its leadership eligibility criteria through the lens of Imam al-Mawardi’s political thought. The research aims to evaluate whether the existing legal framework adequately reflects the moral and intellectual standards emphasized in Islamic governance. Employing a qualitative approach with a normative juridical method, the study conducts a comparative analysis between the administrative and legal requirements for village head candidates and the leadership principles outlined by al-Mawardi. The findings reveal that while the law ensures compliance with legal and technical criteria, it lacks sufficient emphasis on moral integrity (‘adalah) and intellectual competence—two key qualities stressed by al-Mawardi. This research highlights the gap between modern legal frameworks and classical Islamic governance models, suggesting the need for a more comprehensive leadership selection process that integrates ethical and intellectual dimensions. The originality of this study lies in its critical assessment of contemporary village leadership regulations using classical Islamic political thought, offering a unique perspective on governance. The implications of these findings are significant for policymakers and scholars, as they emphasize the necessity of refining leadership criteria to align with both traditional Islamic values and modern governance needs.